Accounting Of Mudharabah Transactions According To Islamic Concepts - Novita, Reetna Ari (JAKI : Jurnal Akuntansi, 2024)
The objective of this research is to investigate the use of the mudaraba accounting framework in the financing model for Micro, Small, and Medium Enterprises (UMKM). The research conducted is a literature review. This study employs a qualitative descriptive model. The utilization of mudaraba accounting as a funding model for the Microfinance Program (PKM) by Islamic Financial Institutions (LKS) in support of Micro, Small, and Medium Enterprises (UMKM). The present study employed Statement of Financial Accounting Standards (PSAK) 105: Accounting for Mudaraba as a framework for the identification, quantification, and representation of PKM transactions using MSMEs. The findings indicate that the financing model for micro, small, and medium enterprises (UMKM) implemented by the PKM contributes to the enhanced self-sufficiency of MSMEs in fulfilling their financial needs for company operations. The support of suitable accounting practices is crucial for enhancing the reliability of information in LKS's Mudaraba-based finance portfolio for MSMEs. Additional study is necessary to investigate the actual circumstances surrounding the financing of Small and Medium Enterprises (SMEs) through the Limited Liability Company (LKS) structure. This research aims to provide a full understanding of the accounting practices associated with mudaraba, a financial arrangement based on profit sharing, which serves as a means to support such financing.